Penerapan Metode Certainty Factor Pada Sistem Pakar Diagnosa Penyakit Diabetes Melitus - Ahlan Ismono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Diabetes Mellitus is a disease that occurs in metabolism at a chronic level. Diabetes Mellitus has always been a frightening disease for the community, this is because diabetes mellitus is a disease that causes death with a fairly high risk of death. Early diagnosis of diabetes mellitus or the community to find out diabetes mellitus is very important. Early diagnosis that is carried out causes early problems, especially for the community. This is because to carry out an examination of diabetes mellitus, laboratory tests must be carried out in hospitals, carry out an overall body examination and the costs are quite high. In addition, there is also limited information by the public on the signs or symptoms that allow a person to be indicated for diabetes mellitus. Therefore, it is necessary to solve these problems to assist in the early diagnosis process by the community. An expert system is a system that is already part of computerization. Computerized expert systems can diagnose certain diseases based on the knowledge stored in the expert system. The certainty factor method is one method that can be used in the process of solving the expert system. The certain factor method can produce an accurate value based on the symptom weight value that has been selected by the patient. The results of the study found that the accuracy value obtained from the process of diagnosing diabetes mellitus was 94,78%.